Reabsorção radicular apical em decorrência do tratamento ortodôntico detectada por meio de tomografia computadorizada de feixe cônico - CASTRO, Iury Oliveira (2012)
Objective: To determine the frequency of apical root resorption in different tooth groups after the end of orthodontic treatment, detected by cone beam computed tomography. Methodology: Images of cone beam computed tomography of 30 patients who had Class I malocclusion and crowding were obtained before and after orthodontic movement. The treatment with fixed appliances was developed based on the Roth prescription. A total of 1256 dental roots were evaluated based on the measurement of linear length between root apex and incisal/cusp. It was an epidemiological, prospective, longitudinal and intra individual study. Results: The mean age of patients was 13 years, 11 were male and 19 female. One hundred percent of the patient presented teeth with apical root resorption, 46% of the roots avaluated was affected. The teeth showed higher extent of apical root resorption were upper lateral incisors, lower lateral, upper central, lower central, upper and lower first molars (p <0.05). By analyzing the roots individually, there was a high frequency of apical root resorption in maxillary central incisors (73%), maxillary lateral incisors (73%), mandibular central incisors (72%), mandibular lateral incisors (70%) and distal roots of mandibular first molar (63%). There was a low frequency of apical root resorption in the buccal roots of the maxillary second premolar (17%), distovestibular and palatine roots of maxillary second molar (18%) and distal roots of mandibular second molar (20%). The results showed that there was no association between frequency of resorption and gender (p> 0.05). The number of resorption did not vary with age when evaluated at age 11 to 16 years (p> 0.05). Conclusion: The apical root resorption was detected in 46% of the roots of teeth submitted to orthodontic treatment, diagnosed by cone beam computed tomography. The most affected teeth were central incisors, lateral and first molars.